Rozwój funkcji administracyjnych Szadku. Rys historyczny - Lamprecht, Mariusz; Sikora, Anna (Biuletyn Szadkowski, 2008)
Szadek, one of the oldest towns in the Łódź region, grew on the crossing of mediaeval routes connecting such cities as Piotrków, Uniejów, Łęczyca and Sieradz. Such location, strategic in terms of communication links, was favourable to Szadek’s development and contributed to the strengthening of its role as an urban settlement performing central functions for the surrounding areas, particularly with regard to administration of territorial (the seat of local government of various levels), judicial and ecclesiastical affairs. There is evidence suggesting that as far back as the 12th century Szadek was functioning as a local administrative and economic centre. In the following centuries it became a major settlement unit providing diverse important functions to the whole district. Today Szadek is a small town which retained only a few of these functions, but nevertheless they reflect its former status on the map of the region. The broad range of services provided by Szadek indicates that it was perceived as a special place in the settlement network. Its changing role and importance as regards the functions performed the historical events which mostly had negative consequences for the town, conducing to its diminished importance on the admministrative map of the region and the country.